Ukraine-Canada: Milestones of Cooperation in the Global World - Fisanov, Volodymyr; Makukh-Fedorkova, Ivanna (Mediaforum : Analytics, Forecasts, Information Management, 2021)
Makar V. Bilateral relations between Ukraine and Canada: formation, development, prospects of dynamics. Chernivtsi: Yuriy Fedkovych Chernivtsi National University, 2020. 496 p.